Effects of torrefaction conditions on the hygroscopicity of biochars. (June 2021) - Jiang, Hewei; Ye, Yangtian; Lu, Ping; Zhao, Mingxing; Xu, Guiling; Chen, Dandan; Song, Tao
Abstract: Agroforestry biomass involving cedar wood (CW), polar wood (PW), corn stalk (CS) and wheat straw (WS) was torrefied in a fixed-bed reactor under the torrefaction temperature ( T ) of 200–300 °C and the holding time ( τ ) of 10–60 min to prepared straw biochars (WSC, CSC) and woody biochars (PWC and CWC). The effects of biomass species, torrefaction temperature and holding time on the hygroscopicity of biochars were investigated under constant temperature and humidity. Combined with the results of N2 adsorption/desorption and FTIR of raw biomass and its biochars, the mechanism of torrefaction conditions on the hygroscopicity of biochar was discussed. The obtained results indicated that water absorption process of biochar can be divided into two stages of initial rapid water absorption and the later slow water absorption. The equilibrium moisture content (EMC) decreases, the hygroscopicity reduction extent (HRE) increases gradually, and hydrophobicity of biochar is enhanced with increasing torrefaction temperature. However, too high torrefaction temperatures ( T  ≥ 275 °C) has little or even adverse effect on the hydrophobicity of biochars. The longer holding time has a certain influence on the hydrophobicity of biochar, but the overall effect is not significant. The hydrophobicity of woody biochars (PWC and CWC) is better than that of straw biochars (WSC and CSC) at the same torrefaction conditions. The severe torrefaction of T  ≥ 275 °C and τ  ≥ 40 min are able to improve the hydrophobicity of woody biochars, however it has negative effect on straw biochars. The hydrophobicity of four biochars is ordered as PW > CW > WS ≈ CS at the same torrefaction conditions. The water adsorption mechanism of biochars is influenced by the coupling effects of physical structure evolution, release of hydrophilic oxygen-containing functional groups and pyrolytic tar condensation, and the severer the torrefaction, the more significant the influence is. Highlights: Water absorption process of biochar involves two stages of initial rapid water absorption and later slow water absorption. The effect of torrefaction temperature on hydrophobicity of biochar is significantly stronger than that of holding time. The order of hydrophobicity of biochar torrefied at same condition is poplar wood > cedar wood > wheat straw ≈ corn stalk.